Stream Theory - Otieno, Godfrey (Journal of Physical Sciences, 2024)
Purpose: The main objective of this research was trying to solve the misunderstood nature of light by introducing and studying fluid optic and its influence on physical science. Methodology: The research adopted observation and a study of already published online and school library books on optics and physical science. Observation is always the best approach to quote a natural occurrence and behavior, the researcher observed the behaviour of thin light by isolating themself for a long time in a dark room having roof holes. Findings: The research findings revealed that; light is not basically a wave, a particle or a photon. Light is sensibly a fluid. Fluid optics has no assumptions and weaknesses as other earlier optical theories as fluid optics clearly brings the channels of light (The streams) and its close link, agreement and influence on physical science as physical nature is brought into focus. Unique contribution to Theory, Practice and Policy: Stream theory completely solves the mystery of light and brings proper understanding of optics now fluid optics. Adoption of the theory and its concepts completely exposes physical science into focus with ease in understanding the natural phenomenon related to optics as the theory avoids assumptions and connects geometrical optics and physical optics to one singular optical study (fluid optics) as a step to singularity achievement in physics. (It is that and it happened that way).